The Evaluation of English Textbook for Ninth Grade Students of Junior High School Entitled: Bahasa Inggris: “Think Globally Act Locally” - Wela, Anjela; Endang, Susilawati; Surmiyati, Surmiyati (Jurnal Indonesia Sosial Sains, 2025)
This research intended to determine the components of the scientific approach included in learning activities of the English textbook entitled Bahasa Inggris "Think Globally Act Locally". This study also described the kind of learning activities of the book that apply the scientific approach. This study belongs to qualitative descriptive research; therefore, the writer used an observation checklist as a technique of data collection and content analysis as the tool of data analysis. The findings showed that the English textbook Bahasa Inggris: "Think Globally Act Locally" has 95 learning activities throughout all book chapters that included components of the scientific approach, including observing, questioning, experimenting, associating, and communicating activities. The findings also showed the repetition and similarity of instruction in learning activities, including Reflecting and Communicating activities, through eleven book chapters. However, the writer argues that this book could be considered a good ELT textbook. However, it still needs improvement to make the learning activities more varied, especially reflection and communication.